Maternal–child consumption of ultra-processed foods and sugar-sweetened beverages in informal settlements in Mumbai, India - Aarti Kumar; Rachel J. Kulchar; Nehaa Khadka; Charlotte Smith; Piyasree Mukherjee; Erika Rizal; Karen Sokal-Gutierrez (Journal of Health, Population and Nutrition, 2023)
Abstract Background The global nutrition transition is associated with increased consumption of ultra-processed snack foods and sugar-sweetened beverages (UPF/SSB), contributing to the double burden of child obesity and undernutrition. Methods This cross-sectional study describes the prevalence of maternal and child UPF/SSB consumption and the factors associated with frequent consumption in a convenience sample of 749 children ages 6 months through 6 years and their mothers participating in a community-based child oral health program in five informal settlement communities in Mumbai, India. Mothers were interviewed regarding maternal and child oral health and nutrition characteristics, including consumption of beverages and foods associated with tooth decay—milk, soda, tea with sugar, sweets, and chips/biscuits—using standardized questionnaires. Spearman correlations were used to assess for associations between various social factors and the frequency of maternal and child consumption of the five food categories. Chi-square tests were used to assess differences in child consumption patterns by age groups. Results Though reported soda consumption was low among both mothers and children, nearly 60% of children consumed sweets and chips/biscuits daily, four to five times the rate of mothers. Factors associated with children’s frequent consumption of UPF/SSB included lower maternal education level, frequent maternal consumption of UPF/SSB, greater number of household members, greater amount of money given to the child, and closer proximity to a store. Conclusion Our findings demonstrate social factors that may promote UPF/SSB consumption. The nutritional dangers of sugary drinks and non-nutritious snacks for mothers and young children should be addressed across maternal–child health, education, and social service programs. Early childhood nutrition interventions should involve the entire family and community and emphasize the need to limit children’s consumption of unhealthy foods and beverages from an early age.